Localization and translocation of mature miRNAs - A.E. Abaturov; V.L. Babуch (Zaslavsky O.Yu., 2021)
The scientific review shows the ways of nuclear import and export of miRNAs in the cell. The authors present a clear and accessible scheme of microRNA translocation in the cell. The article shows that the main site of localization in the cytoplasm of cells of the RISC complex and its components, including miRNAs, are processing P-cells. The authors cite the fact that Argonaute proteins - signature components of the effector complex of RISC RNA interference - are localized in mammalian P-bodies. It is shown that proteins of the karyopherin family mediate the translocation of miRISC into the cell nucleus. These proteins recognize nuclear localization sequences (NLS) in the amino acid sequences of proteins and actively transport these proteins through the pores of the cell's nuclear membrane. It is emphasized that in addition to non-selective mechanisms of nuclear import of miRNAs, there are transport mechanisms that carry certain miRNAs across the cell membrane. Some miRNAs are presented, which are mainly localized in the nucleus of a certain type of cell. Scientists believe that much of the nucleus miRNA is concentrated in polysomes. Export of nuclear pool microRNA into the cytoplasm of the cell occurs with the help of export 1. Thus, in the cytoplasm of the cell, mature forms of microRNA accumulate, some of which are translocated to the cell nucleus or the extracellular space. Assembly of the miRISC complex is carried out in the cytoplasm of the cell, and only after the formation of the complex, it is imported into the cell nucleus. The spectrum of exosome-associated miRNAs can be a highly important diagnostic criterion for some nosologies, and exosomes containing certain miRNAs can be used for targeted therapy of specific diseases. To write the article, information was searched using databases Scopus, Web of Science, MedLine, PubMed, Google Scholar, EMBASE, Global Health, The Cochrane Library, CyberLeninka.